Influence of nozzle geometry on fluid flow parameters - Penkov, Igor; Aleksandrov, Dmitri (Zielona Góra: Uniwersytet Zielonogórski)
The article discusses ways for optimization of a standard nozzle cup design to achieve a narrower paint flow. The analysis of a standard nozzle cup shows that distribution of air pressure is critically uneven both along the nozzle axis and in the radial direction. A decrease in pressure is about 45% at the distance of 2 mm from the front surface of the nozzle cup.
Keywords: fluid flow simulation; nozzle geometry; optimization